The ultimate preparation materials, complete vocabulary, flash cards, general practice tests : korean english dictionary word to word - Ph.D. Kendall K. Thompson ([Place of publication not identified] : [Publishers name not idntified])
IELTS, which stands for International English Language Testing System, is a globally-recognised test of English language. Many people are aware that having the right IELTS score is one way of proving that you have the English language proficiency to enter a top university, but did you know that IELTS scores are also used by governments and professional bodies for immigration and professional registration purposes? So getting the right IELTS score is important for many people for many different reasons.
Keywords: PREPARATION MATERIALS; KOREAN ENGLISH DICTIONARY; VOCABULARY